Laparoscopic liver resection for large hepatocellular carcinoma - Tsai, Kuei-Yen; Huang, Ming-Te (Laparoscopic Surgery, 2018)
In the journal Surgical Endoscopy, Levi Sandriand Spoletini et al. reported a two-center experience with the short-and long-term outcomes of laparoscopic liver resection (LLR) for largehepatocellular carcinoma (HCC) (1). A total of 172 patients from twohigh-volume liver surgery centers who underwent LLR between 2003 and 2016 wereanalyzed after classification into three groups according to tumor size (